PENDEKATAN METODE PENYULUHAN PERTANIAN USAHA TANI CABAI DI DESA TIWOHO KECAMATAN WORI KABUPATEN MINAHASA UTARA - Patrix Juriko Tumurang; Melsje Yellie Memah; Melissa Lady Gisela Tarore (AGRI-SOSIOEKONOMI, 2019)
The purpose of this study was to determine the appropriate approach to agricultural extension methods of chili farmers in Tiwoho Village, Wori District. This research was conducted from October to December 2018. The data used in this study are primary data and secondary data. Theprimary data collection method is done by asking respondents to fill out a questionnaire that uses a Likert Scale measurement tool and has been prepared. The sampling technique was done by purposive sampling. The number of respondents is 15 people. Data analysis was carried out descriptively. Secondary data obtained from the Tiwoho Village office and the internet, namely google cendekia to get articles from various scientific journals and theses from other universities related to the topic of this research, especially concerning agricultural extension methods. This study shows that the approach of individual agricultural extension methods is more suitable to have the highest total score as many as 314 and a percentage of 83.7%.*jnkd+eprm*